2007
DOI: 10.1016/j.addbeh.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptomatology among individuals in alcohol detoxification treatment

Abstract: The coexistence of psychiatric symptomatology among individuals receiving longer-term treatment for alcohol use disorders has been well-established; however, less is known about comorbidity among individuals receiving alcohol detoxification. Using the Brief Symptom Inventory (BSI; Derogatis, 1992), we compared psychiatric symptomatology among 815 individuals receiving short-term detoxification services with normative data from nonpatients, psychiatric patients, and out-oftreatment individuals using street drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
12
1
3
Order By: Relevance
“…Furthermore, in the latter study, the frequencies of the following diagnoses were also similar to those found in the present study: depressive disorders (33.9%), anxiety disorders (11.5%), personality disorders (16.1%) and schizophrenia (2.6%). In Group 1, 72% of patients had a certain diagnosis of CMBD, a result that was lower than those observed in another clinical study carried out in Alaska, USA, conducted in patients with the same period of abstinence in an alcohol detoxification center (82%) 14 . This study used the Brief Symptom Inventory as a diagnostic tool and showed frequencies of diagnoses of depressive disorders (74.2%) and anxiety CMBD in chemically dependent patients disorders (73.5%) that were higher than those observed in the present study.…”
Section: Frequency Of Diagnosis Of Cmbd Associated With CDcontrasting
confidence: 61%
See 2 more Smart Citations
“…Furthermore, in the latter study, the frequencies of the following diagnoses were also similar to those found in the present study: depressive disorders (33.9%), anxiety disorders (11.5%), personality disorders (16.1%) and schizophrenia (2.6%). In Group 1, 72% of patients had a certain diagnosis of CMBD, a result that was lower than those observed in another clinical study carried out in Alaska, USA, conducted in patients with the same period of abstinence in an alcohol detoxification center (82%) 14 . This study used the Brief Symptom Inventory as a diagnostic tool and showed frequencies of diagnoses of depressive disorders (74.2%) and anxiety CMBD in chemically dependent patients disorders (73.5%) that were higher than those observed in the present study.…”
Section: Frequency Of Diagnosis Of Cmbd Associated With CDcontrasting
confidence: 61%
“…Severe mood disorders that are not treated can lead to relapses and even death by suicide 19 . In addition, it is believed that making a diagnosis of CMBD is important, even in the period of detoxification, as this increases the likelihood of individuals' needs being adequately met and of better adherence to treatment 14 .…”
Section: Frequency Of Diagnosis Of Cmbd Associated With CDmentioning
confidence: 99%
See 1 more Smart Citation
“…La comorbidité la plus importante associe les troubles d'utilisation d'une substance et les troubles dits d'externalisation (Abrantes et al, 2003;Armstrong & Costello, 2002;Couwenbergh et al, 2006;Hawkins, 2009 (Dorard, Berthoz, Phan, Corcos, & Bungener, 2008;Elkington, Bauermeister, & Zimmerman, 2010;Johnson, Brems, Mills, & Fisher, 2007;Lubman, Allen, Rogers, Cementon, & Bonomo, 2007).…”
Section: La Consommation De Psychotropes Et La Comorbidité Psychopathunclassified
“…Most of the work conducted in alcoholic subjects is conducted with abstinent subjects or having started [16] support. The profiles to which lead these studies do not take into account representation alcoholic subjects have their clinical disorders when they imagine drinking.…”
Section: Introductionmentioning
confidence: 99%